ANALISIS EFEKTIVITAS PENGGUNAAN APLIKASI SISTEM PERBENDAHARAAN ANGGARAN NEGARA (SPAN) DALAM MENYALURKAN GAJI INDUK YANG BERSUMBER ANGGARAN PENDAPATAN DAN BELANJA NEGARA (APBN) DI KANTOR PELAYANAN PERBENDAHARAAN NEGARA (KPPN) MEULABOH - Yani, Fitri; Fatmayanti, Fatmayanti; Sianturi, Daniel (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Universitas Jabal Ghafur, 2022)
This study aims to identify problems that occur during the process of distributing APBN funds, one of which is the main salary using the SPAN application. The research design uses a qualitative descriptive design, this research was conducted at KPPN Meulaboh where the office is one of the sources for researchers in conducting interviews and collecting data in the process of distributing the main salary. The interview results show that the SPAN application has not been running effectively because there are still various shortcomings or obstacles in the process of disbursing the main salary that is felt by the Meulaboh KPPN staff such as an inadequate network that hampers office work and also inflexible job placement where the work can only be done at the office. . As for some that were analyzed, such as the effectiveness of using the SPAN application, comparisons between the manual system and SPAN, and also wanted to see the advantages and disadvantages of the two systems. Then the formulation in making policies on what are the problems in processing the main salary sourced from the APBN in using the SPAN application.Keywords: SPAN, Main Salary, APBN.